Is Gamification a Magic Tool?: Illusion, Remedy, and Future Opportunities in Enhancing Learning Outcomes during and beyond the COVID-19 - Oe, Hiroko; Takemoto, Takuji; Ridwan, Muhammad (BIRCU, 2020)
Gamification in education has been discussed with potential for further implementation at universities; however, practical suggestions concerning which key issues educators need to consider has far not been shared in academia. This study applied a qualitative approach using interview data with 24 students who participated in the business class with games as learning measures. It has found that most of them believed that gamification could be useful in reinforcing key themes and topics after having learnt them through traditional means: They appreciated the games as a supportive measure to ‘glue’ key knowledge to their learning. A significant drawback that they emphasised was that taking notes is not easy while they are involved in games, which made them unconfident and uncertain about the learning outcome. As a result, a conceptual framework for pedagogy stakeholders was proposed for further discussion of how to design a gamification-based curriculum effectively.